Proteomics Approach Reveals Seed Germination Mechanism in Model Plants - Zaynab, Madiha; Noman, Ali; Fatima, Mahpara; Saleem, Tahira; Abbas, Safdar; Raza, Ammar; Iqbal, Muhammad Naeem (PSM Microbiology, 2018)
Seed germination is a complex process which occurs by the successful regulation of different factors necessary to regulate germination in a coordinated and sequential way, such as phytohormones. Among three phases of seed germination, the second phase is the most important due to reactivation of metabolic pathways. DELLAs accumulation in seed resulted in the expression of gene related to F box protein. Gibberellins receptor, GIBBERELLIN INSEN-STIVE DAWRF1 (GID1) protein in rice, and F box are involved in Della degradation in the nucleus. In this mini-review, we summarize the protein related to the rice seed germination, such as protein related to energy and carbohydrate metabolism. In spite of several studies conducted to understand the genomic, transcriptomic, and metabolomics data still we are unable to understand the mechanism of seed germination. To uncover the underlying mechanism of germination, current challenges and future perspectives we write this review, which might be helpful to understand the complex process of seed germination.